High-capacity activated carbon anode material for lithium-ion batteries prepared from rice husk by a facile method - Yu, Kaifeng; Li, Jian; Qi, Hui; Liang, Ce (Diamond and related materials, 2018)
In this paper, rice husk was selected as raw materials to prepare activated carbon via an effective and facile method. NaOH, as an activator, plays a crucial role in forming the hierarchical porous structure in this method. These materials were characterized through X-ray diffraction (XRD), Raman spectroscopy, Nitrogen adsorption-desorption analyses, Scanning electron microscopy (SEM) and Transmission electron microscopy (TEM). The electrochemical properties have varied with the changes of morphology and structure after the activation process. After 100 cycles at a rate of 0.2C, the reversible specific capacity of rice husk-derived activated carbon (denoted as RHAC) stabilized at 448 mAhg−1. In addition, the RHAC electrode delivers an excellent rate capability with the discharge capacities of 652, 477, 363, 242 and 197 mAhg−1 at 0.2C, 0.5C, 1C, 2C, 5C, respectively. Compared with the non-activated materials (denoted as RHC), the significantly improved electrochemical performance of the RHAC could be attributed to the hierarchical porous structure with more edges, defects and the enlarged surface area. Rice husk-derived activated carbonaceous anode material was synthesized by a facile method. Its unique porous structure plays an important role in the improvement of electrochemical performance. [Display omitted] •We report an activated carbon anode material derived from rice husk via a facile method.•This low-cost and environment-friendly method has potential application in biomass waste treatment.•This biomass electrode delivers excellent performances with high capacity and superior rate capability.